Aktorzy i Szekspir. O pewnym motywie w polskim filmie - Jazdon, Mikołaj (Przestrzenie Teorii, 2019)
Jazdon Mikołaj, Aktorzy i Szekspir. O pewnym motywie w polskim filmie [Actors and Shakespeare or About a Certain Motif in Polish Film]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 15–44. ISSN 1644-6763. DOI 10.14746/pt.2019.32.1. This article deals with various references to William Shakespeare’s plays in Polish postwar films, both theatrical and television ones. There are no Polish film adaptations of Shakespeare’s works except for television dramas made for the Television Theater on state TV. There are, however, Polish films (mainly from 1962–1989) about actors and performing arts with fragments and motifs from Shakespeare plays. Their characters are often actors deprived by fate (or History) of the chance to play a Shakespeare role on stage and forced to play it in life instead.